Philosophical attitudes of the early works of P. Tychyna as an object of modernist-postmodern myth creation - H. V. Vdovychenko (Ukrainian Cultural Studies, 2019)
The article classifies and highlights three stages spanning the last hundred years – pre-Soviet, Soviet and post-Soviet, of research and mythologization of the life and creation of P.Tychyna, using the example of studying the philosophical attitudes of his early work in the Ukrainian state, the Ukrainian SSR, Ukraine and abroad. The specifics of the formation of the mentioned stages during 1918 – 2019 were systematically considered on materials, including little-known, studies of more than fifty representatives of domestic and foreing tychynology, as well as a wide range of materials of the poetic, prosaic, scientific-journalistic and epistolary heritage of P. Tychyna and his contemporary colleagues. In the context of this review an attempt was made of critical interdisciplinary analysis – cultural and philosophical and literary, of the ideological foundations and the results of the modernist and postmodern mythologization of the early creativity of P. Tychyna as the leading creator and symbol of Ukrainian Modernist and Socialist-Realistic literature and, in general, cultural development. The article identifies three leading aspects of defining and studying the philosophical foundations of P. Tychyna’s early work in the twentieth – early twenty first centuries: 1) the absence of the formulation and systematic development of the topic in P. Tychyna studies, except for the initial attempts at each of its stages, so far; 2) the narrow specialty of individual attempts at such research, first of all, almost entirely literary or linguistic, but not professional philosophical and cultural philosophical; 3) the dominant conditionality of the major achievements of almost all of these studies, mainly the Soviet period, the political environment of the development of national humanities and, as a consequence, the consistent isolationist-Soviet-anti-European mythology of P. Tychyna’s creative figure and heritage. In view of this, the development of this topic in the context of an interdisciplinary, critically-demythologizing scientific search, formed in the contemporary P. Tychyna studies, has been identified as promising.